STRATEGI PEMBERDAYAAN MASYARAKAT DI KAWASAN JATIGEDE OLEH PEMERINTAH KABUPATEN SUMEDANG - Riswati, Riswati; Susilawati, Susilawati (Jurnal Politik Pemerintahan Dharma Praja, 2018)
ABSTRACT Community empowerment in Jatigede Reservoir area, need to be done as soon as possible by PemerinahSumedang Regency, Community Empowerment aimed is to menandarikan community, so that society can be independent and empower to fulfill requirement of her life, Impact of Jatigede Reservoir development, impact very wide for society Jatigede area, where initially they have agricultural land and they can cultivate the land intended to meet their daily needs, but after the construction of Jatigede Reservoir, most of the people around the area, currently have no jobs, and income to meet their daily needs, for that writer interested to conduct research area around Jatigede Reservoir, and method which writer use is qualitative analysis, and descriptive analysis. By using SWOT method. The results obtained are, where community empowerment conducted by the Government of Sumedang Regency, has not been maximized, and has not impacted to be able to change and improve the economic condition of the community around the Jatigede Reservoir Area. Based on the above description, Sumedang District Government needs to prepare a strategic plan that contains the empowerment program as a first step through an analysis of the environment both internal (Strengths and Weaknesses) and external (Opportunities and Threats). So the author menyaranan for Government District Sumedang, to be more serious and consistent and effective in providing empowerment to the community around the area at Jatigede Reservoir. So the community can be empowered to meet the needs of daily life. Keywords: community empowerment strategy.